Characterization and pathogenicity of a novel avian orthoreovirus in China - Chen, Shunyan; Yang, Jialin; Li, Li; Guo, Yawei; Yang, Shenghua; Su, Zetao; Zhao, Sucan; Li, Xuesong; Lin, Wencheng; Du, Yunping; Yin, Lijuan; Wang, Lianxiang; et al. (Frontiers in Microbiology, 2025)
IntroductionAvian orthoreovirus (ARV) is a significant pathogen causing viral arthritis, leading to substantial economic losses in the poultry industry worldwide.MethodsA novel ARV strain, designated FJ202311, was isolated from a broiler farm in Fujian Province, China. Whole-genome sequencing was conducted using next-generation sequencing with MGI technology, and phylogenetic analysis of the sigma C amino acid sequence was performed. Comparative sequence analysis identified unique genetic features of FJ202311. Pathogenicity studies were carried out by inoculating broilers with the isolated strain and monitoring clinical signs, weight gain, and histopathological changes.ResultsThe complete genome of FJ202311 was determined to be 23,495 base pairs in length, encoding 12 major proteins. Phylogenetic analysis revealed that FJ202311 forms a distinct genotypic cluster, exhibiting only 47.1% to 59.3% sequence identity to 16 reference ARV strains. Notably, 50 unique amino acid substitutions were identified in the sigma C protein. Pathogenicity tests demonstrated that FJ202311 caused severe arthritis and tenosynovitis in broilers. Infected birds exhibited significant weight loss compared to controls, with reductions of 11.78% and 8.93% at 14 and 21 days post-infection, respectively.DiscussionThis study highlights the unique molecular and pathogenic characteristics of the novel ARV strain FJ202311, contributing to our understanding of ARV diversity and epidemiology in China. These findings underscore the importance of continuous monitoring and provide insights for developing improved prevention and control strategies against ARV.